2003
DOI: 10.1002/art.11449
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the thrombogenic and inflammatory properties of antiphospholipid antibodies by fluvastatin in an in vivo animal model

Abstract: Methods. Two groups of CD-1 male mice, each comprising ϳ18 mice, were fed either normal saline solution or 15 mg/kg fluvastatin for 15 days. Each of the 2 groups was further subdivided to receive either purified IgG from patients with the antiphospholipid syndrome (IgG-APS) or normal IgG from healthy subjects. Analysis of thrombus dynamics was performed in treated and control mice, using a standardized thrombogenic injury procedure, and the area (size) of the thrombus was measured. Adhesion of leukocytes to EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 66 publications
6
77
0
3
Order By: Relevance
“…Indeed, micromolar concentrations of gemcitabine and fluvastatin have been reached in human plasma in pharmacokinetic studies (Kroep et al, 1999;Kantola et al, 2000), and these plasma levels are in the range of the antiproliferative activity found in the present study. Moreover, the administered fluvastatin dose in our in vivo experiment was based on the study by Ferrara et al (2003), who showed, for the same total dose given in 14 days, serum concentrations of fluvastatin in mice higher than 1.2 mg ml À1 , representing drug levels of B2 times the mean drug concentration in human plasma after a 40 mg oral dose and confirming the potential translation to the clinic of our data. The chemotherapeutic activity of gemcitabine is well known (Bergman et al, 1996), and has been confirmed by MIA PaCa2 cells used in this study, whereas the antiproliferative activity of fluvastatin has been previously described only in breast cancer cells .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, micromolar concentrations of gemcitabine and fluvastatin have been reached in human plasma in pharmacokinetic studies (Kroep et al, 1999;Kantola et al, 2000), and these plasma levels are in the range of the antiproliferative activity found in the present study. Moreover, the administered fluvastatin dose in our in vivo experiment was based on the study by Ferrara et al (2003), who showed, for the same total dose given in 14 days, serum concentrations of fluvastatin in mice higher than 1.2 mg ml À1 , representing drug levels of B2 times the mean drug concentration in human plasma after a 40 mg oral dose and confirming the potential translation to the clinic of our data. The chemotherapeutic activity of gemcitabine is well known (Bergman et al, 1996), and has been confirmed by MIA PaCa2 cells used in this study, whereas the antiproliferative activity of fluvastatin has been previously described only in breast cancer cells .…”
Section: Discussionsupporting
confidence: 79%
“…The mice were randomised into groups of five. In order to treat an established tumour (B35 mm 3 ), at day 15 from the cell inoculum, fluvastatin, gemcitabine or their simultaneous combination was administered intraperitoneally as follows: (1) fluvastatin every 2 days at a dose of 30 mg kg À1 for 14 days (cumulative dose of 210 mg kg À1 per mouse equivalent to the study by Ferrara et al, 2003); (2) gemcitabine 120 mg kg À1 four times at 3-day intervals as described previously (Braakhuis et al, 1995); (3) combination treatment of fluvastatin and gemcitabine. The control group was injected i.p.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Statin-treated animals developed thrombi no larger than those formed in control mice infused with normal human IgG (135). In separate studies, fluvastatin has been shown to decrease leukocyte-endothelial adhesion in postcapillary venules (135). Fluvastatin also significantly decreases expression of tissue factor by HUVECs exposed to human antiphospholipid antibodies (136).…”
Section: Abeles and Pillingermentioning
confidence: 96%
“…Fluvastatin decreased anti-␤ 2 -glycoprotein I-mediated endothelial activation in vitro (but not in the presence of mevalonate) (134), and prevented large thrombi from forming in an animal model of antiphospholipid antibody syndrome (infusion of mice with human IgG antibodies from patients with antiphospholipid syndrome) (135). Statin-treated animals developed thrombi no larger than those formed in control mice infused with normal human IgG (135). In separate studies, fluvastatin has been shown to decrease leukocyte-endothelial adhesion in postcapillary venules (135).…”
Section: Abeles and Pillingermentioning
confidence: 99%
“…104 In addition, fluvastatin treatment in animal model with IgG from APS patients significantly reduced size of thrombi and number of adherent leukocytes. 105 Contradictory to this finding, pravastatin was reported not to prevent aPL-related changes in human first trimester trophoblast function. 106 Therefore, it seems to be premature to apply statin treatment in women with aPL and RPL.…”
Section: The Epitopes Of Apl and Treatment Outcomementioning
confidence: 99%